PENGARUH SERVICESCAPE TERHADAP REPURCHASE INTENTION DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI (Survei Pada Konsumen Warung Selat Solo Mbak Lies) - Desty Ratnasari; Marjam Desma Rahadhini; Suprihatmi Sri Wardinings (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the significance of the effects of servicescape on repurchase intention with consumer satisfaction on the consumers of Mbak Lies Solo Strait. This research was conducted at the consumers of Mbak Lies Solo Strait. The type of data used is qualitative and quantitative data. Data sources used are secondary and primary data. The entire population in this study were all consumers of Mbak Lies Solo Strait who could not know the amount. The sample used in this study was taken as many as 70 respondents. The data analysis technique used is classic assumption test, descriptive analysis, multiple linear regression analysis, t test, F test, and coefficient of determination, and Sobel Test. The results of this study indicate that servicescape has an effect on consumer satisfaction. Servicescape has an effect on repurchase intention. Consumer satisfaction mediates servicescape against repurchase intention.